HIV/TB co-infection and availability of health services in relation to socio-economic status - Subba, Bhim Bahadur; Rimal, Nirmal (Journal of Advanced Academic Research, 2018)
The human immunodeficiency virus (HIV) pandemic disproportionate affects especially less developed countries and underprivileged communities. HIV weakens immune system of infected individuals and making them more susceptible to tuberculosis (TB) infection. Both HIV and TB disease are supposed to fuel each other socially and biologically and it is further fuelled by such as poor accessibility to services, illiteracy, stigma and discrimination all these factors have pushed Nepal into more vulnerability. This article aimed to find out the availability and accessibility to the HIV/TB services in relation to socio-economic status of respondents. A cross sectional study was conducted at four HIV care and prevention centers of different non-governmental organizations (NGOs) of Nepal. In the study, 51 samples were selected using random sampling procedures who gave consent to the interview. A pre-tested semi-structured questionnaire was used to collect data. Confidentiality was highly maintained and data were analyzed. The result showed mean age of respondents’ was 36.38 years. The pre-dominant 96.1 percent of respondents were from 18-54 years of age. Respondents from all socio-economic status almost two-third indented to use government hospital than private HIV/TB services. The majority 98.0 percent of HIV infected respondents belonged to destitute to better off economic status and they were further disadvantaged by lack of knowledge and information of HIV/TB services such cluster of differentiation 4 (CD4) and viral load service.